2021
DOI: 10.1111/mec.15859
|View full text |Cite
|
Sign up to set email alerts
|

Molecular control of the floral transition in the mast seeding plant Celmisia lyallii (Asteraceae)

Abstract: Mast flowering (or masting) is synchronous, highly variable flowering among years in populations of perennial plants. Despite having widespread consequences for seed consumers, endangered fauna and human health, masting is hard to predict. While observational studies show links to various weather patterns in different plant species, the mechanism(s) underpinning the regulation of masting is still not fully explained. We studied floral induction in Celmisia lyallii (Asteraceae), a mast flowering herbaceous alpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 104 publications
(164 reference statements)
0
15
0
Order By: Relevance
“…Applying advances in genome-wide transcriptomics (e.g. DNA microarray and RNAseq) [25,64] is also promising to unravel the underlying mechanism of dynamic environmental response of genes and its effect on masting. In fact, a molecular phenology approach that monitors seasonal recurring gene expression patterns in natura [19] has been increasingly used in non-model organisms [21,25,64,65].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Applying advances in genome-wide transcriptomics (e.g. DNA microarray and RNAseq) [25,64] is also promising to unravel the underlying mechanism of dynamic environmental response of genes and its effect on masting. In fact, a molecular phenology approach that monitors seasonal recurring gene expression patterns in natura [19] has been increasingly used in non-model organisms [21,25,64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of these gene families in masting species opens a new direction for the evolution of masting studies, allowing us to elucidate whether species with different life-history strategies and mating systems use similar genetic pathways to produce different phenotypes. Using genomewide transcriptome analysis as a useful first step in describing patterns of gene expression and finding a molecular marker for traits of interest, several studies demonstrated that masting is genetically regulated at the stage of floral transition [22,23,25,64,65]. Monitoring major flowering-time genes (FcFT, FcLFY and FcAP1) in F. crenata Blume (figure 2a) in leaves and buds over 8 years demonstrated that biennial flowering dynamics is caused by on-off cycles in these flowering-time genes (figure 2b), which was highly correlated with fluctuation royalsocietypublishing.org/journal/rstb Phil.…”
Section: Is There Evidence For Genetic Regulation Of Masting Traits?mentioning
confidence: 99%
See 3 more Smart Citations